Nonparametric estimation for stationary and strongly mixing processes on Riemannian manifolds - Gbaguidi Amoussou, Amour; DJIBRIL MOUSSA, FREEDATH LAYE; Ogouyandjou, Carlos; Diop, Mamadou Abdoul (My University, 2022)
In this paper, nonparametric estimation for a stationary strongly mixing and manifoldvalued process (X j ) is considered. In this non-Euclidean and not necessarily i.i.d setting, we propose kernel density estimators of the joint probability density function, of the conditional probability density functions and of the conditional expectations of functionals of X j given the past behavior of the process. We prove the strong consistency of these estimators under sufficient conditions, and we illustrate their performance through simulation studies and real data analysis.
Keywords: Riemannian manifolds · Nonparametric estimation · Kernel density; estimation · Stationary and strongly mixing processes · Strong consistency